FACE IN PYTHON PROGRAMMING LANGUAGE DETERMINATION AND IDENTIFICATION (European Journal of Interdisciplinary Research and Development, 2022)
Python is becoming an increasingly popular programming language. It's a free, high-level language with a very flat learning curve. It has an extensive collection of libraries that can be used for free. This article will first discuss computer vision libraries. Then the face detection and face recognition capabilities of existing libraries are analyzed. The basic description of the algorithm used in libraries is given. An example of the resulting image is provided for each key step. Although only two sample images are given in the paper, the algorithm has been analyzed on many images. The analysis confirmed that Python is indeed the tool of choice for face detection and recognition tasks.